2016
DOI: 10.1007/s13197-015-2065-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dough rheological properties and bread texture of pearl millet-wheat flour mix

Abstract: Absract This study was undertaken with the objective of formulating composite bread using pearl millet (Pennisetum glaucum) and wheat (Triticum aestivum) flours . Rheological and bread making properties of composite flours were evaluated. Mixolab results revealed torque increased and dough stability time decreased upon incorporation of pearl millet flour in wheat flour. The incorporation of millet flour at optimum level (5 %) led to an increase of the dough strength (W) and the elasticity-to-extensibility rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
(20 reference statements)
3
29
0
Order By: Relevance
“…Similar results were found by Seghchi et al (2001), where the bread specific volume increased up to a certain level with mushroom substitution and then decreased gradually with the increased percentage of mushroom content. To be specific, it is able to develop lipid monolayers at the gas or liquid interphase of the gas cells and, as a result, increases the ability of the dough to retain gas (Maktouf et al, 2016). The findings of Ulziijargal et al (2013) illustrated that the specific volume of bread substituted with mushroom mycelium was much lower than the control bread and resulted in a smaller sized loaf of bread.…”
Section: Effect Of Mushroom Powder On the Physical And Texture Propmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found by Seghchi et al (2001), where the bread specific volume increased up to a certain level with mushroom substitution and then decreased gradually with the increased percentage of mushroom content. To be specific, it is able to develop lipid monolayers at the gas or liquid interphase of the gas cells and, as a result, increases the ability of the dough to retain gas (Maktouf et al, 2016). The findings of Ulziijargal et al (2013) illustrated that the specific volume of bread substituted with mushroom mycelium was much lower than the control bread and resulted in a smaller sized loaf of bread.…”
Section: Effect Of Mushroom Powder On the Physical And Texture Propmentioning
confidence: 99%
“…The lipid content of bread has been reported to contribute to the differences in loaf volume (especially the polar lipid fraction). To be specific, it is able to develop lipid monolayers at the gas or liquid interphase of the gas cells and, as a result, increases the ability of the dough to retain gas (Maktouf et al, 2016). In addition, the different nutrient compositions for the doughs had different influences on the proliferation of yeast growth and gas production during the fermentation process, thus, influencing loaf volume (Ammar et al, 2016).…”
Section: Effect Of Mushroom Powder On the Physical And Texture Propmentioning
confidence: 99%
“…Gavurníková et al (2011) and Maktouf et al (2016) reported that there is decline in DDT on increment of level of millet flour in wheat flour. Dough should be optimally developed and should possess the strength to hold steam accounting for higher puffing height of chapatti.…”
Section: Empirical Rheology Of Wheat and Finger Millet Flourmentioning
confidence: 99%
“…Crumb volume represents the capability of retaining leavened gas within the dough mass (Onyango et al, 2009) as well as it is an important quantitative parameter for baking performance (Maktouf et al, 2016;Mondal & Datta, 2008). Crumb specific volume (cm 3 /g) is related to crumb hardness and relative elasticity (Scanlon & Zghal, 2001).…”
Section: Resultsmentioning
confidence: 99%